Novice Investors Intention To Use XBRL With Age, Gender, And Experience As Moderating Variables - Baswara, Satsya Yoga; Wibowo, Yureza Rian; Purnomo, Gabriel Dading (Economic Education Analysis Journal, 2021)
The purpose of this study was that novice investors could take the results of this study into consideration for using XBRL-based financial reports which were more flexible than ordinary financial reports. In this study, the behaviour of novice investors in using XBRL financial statements was tested by using the variable performance expectations and facility conditions from the Unified Theory of Acceptance and use of technology (UTAUT) model. The two variables were selected from UTAUT because it was stated that UTAUT was a technology acceptance testing model that was perfect than other technology acceptance models. The population in this study was millenials aged 19 to 28 years old, while the sample was 121. This study used a quantitative method whose data used purposive sampling and for collecting data using questionnaires. For statistical tools, we used WARP PLS for second-order testing and SPSS for the multiple regression. The research showed us that there was a tendency that performance expectations and facility conditions affected the intention of novice investors to use XBRL in processing required financial statement information.